DEVELOPMENT OF PROBLEM-BASED LEARNING E-LKPD WITH EDUCATIONAL GAMES ON INTEGERS - Destiana, Anisya; Rahmawati, Dwi; ES, Yeni Rahmawati (Universitas Muhammadiyah Metro, 2026)
At SMP Negeri 5 Terbanggi Besar, seventh-grade students still show low engagement and understanding of integer material. The student worksheets (LKPD) and textbooks used in learning are visually unattractive and lack interactivity, causing students to become bored easily and less motivated. In addition, the internet facilities available at the school have not been maximized to support more engaging and interactive technology-based learning. This research was conducted at SMP Negeri 5 Terbanggi Besar with seventh-grade students as the subjects. The objectives of this study are: (1) to describe the process of developing an electronic student worksheet (E-LKPD) based on Problem-Based Learning (PBL) supported by educational games using the ADDIE development model, and (2) to determine the validity and practicality of the developed E-LKPD. The development model used is ADDIE, consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. Data collection instruments include interview sheets, expert validation sheets, and student response questionnaires. Validation was carried out by three material experts and three media experts, while the practicality test was conducted with ten seventh-grade students. The result of this research is a PBL-based E-LKPD integrated with educational games to facilitate learning on integer material. The analysis stage identified the needs of teachers and students for learning media, while the design and development stages produced a visually appealing and interactive prototype. Evaluation was conducted through revisions based on feedback from experts and users. The average validation score was 86% (very valid), and the practicality test result was 90% (very practical), indicating that the E-LKPD is feasible and effective for use in the learning process. Di SMP Negeri 5 Terbanggi Besar, siswa kelas VII masih menunjukkan keterlibatan dan pemahaman yang rendah terhadap materi bilangan bulat. LKPD dan buku cetak yang digunakan dalam pembelajaran kurang menarik secara tampilan dan minim interaktivitas, sehingga siswa cepat merasa bosan dan kurang termotivasi. Selain itu, fasilitas internet yang tersedia di sekolah belum dimaksimalkan untuk mendukung pembelajaran berbasis teknologi yang lebih menarik dan interaktif. Penelitian ini dilakukan di SMP Negeri 5 Terbanggi Besar dengan subjek siswa kelas VII. Tujuan dari penelitian ini adalah: (1) untuk mendeskripsikan proses pengembangan Lembar Kerja Peserta Didik Elektronik (E-LKPD) berbasis PBL yang didukung oleh game edukasi dengan menggunakan model pengembangan ADDIE, dan (2) untuk mengetahui validitas dan kepraktisan dari E-LKPD yang dikembangkan. Model pengembangan yang digunakan adalah ADDIE, yang terdiri dari lima tahap: Analyze, Design, Development, Implementation, dan Evaluation. Instrumen pengumpulan data meliputi lembar wawancara, lembar validasi ahli, dan angket respon siswa. Validasi dilakukan oleh tiga ahli materi dan tiga ahli media, sedangkan uji kepraktisan dilakukan kepada sepuluh siswa kelas VII. Hasil penelitian berupa E-LKPD berbasis PBL yang terintegrasi dengan game edukasi untuk memfasilitasi pembelajaran materi bilangan bulat. Tahap analisis mengidentifikasi kebutuhan guru dan siswa terhadap media pembelajaran, sementara tahap desain dan pengembangan menghasilkan prototipe yang menarik secara visual dan interaktif. Evaluasi dilakukan melalui revisi berdasarkan masukan dari ahli dan pengguna. Nilai rata-rata hasil validasi adalah 86% (sangat valid), dan hasil uji kepraktisan sebesar 90% (sangat praktis), sehingga E-LKPD ini dinyatakan layak dan efektif digunakan dalam proses pembelajaran.